Single non-ionic surfactant based self-nanoemulsifying drug delivery systems: formulation, characterization, cytotoxicity and permeability enhancement study. (May 2013) - Bandivadekar, Mithun; Pancholi, Shyamsundar; Kaul-Ghanekar, Ruchika; Choudhari, Amit; Koppikar, Soumya
<x xml:space="preserve">Abstract</x> Single non-ionic surfactant based self-nanoemulsifying drug delivery system (SNEDDS) was formulated and characterised for poor water soluble drug, Atorvastatin calcium. Capmul MCM oil showing highest solubility for Atorvastatin calcium was selected as oil phase. Self-nanoemulsifying capacity of Cremophor RH 40, Cremophor EL, Tween 20, Tween 60, Tween 80 and Labrasol were tested for the selected oil. In vitro dissolution studies were performed and were characterized by t85% and dissolution efficiency (DE). Cytotoxicity of the formulations and permeation enhancement of the drug across caco-2 cell monolayer was assessed. Capmul MCM was found to be better nanoemulsified in decreasing order of Cremophor RH 40 > Cremophor EL > Tween 20 > Tween 60 > Tween 80. Values of droplet size (range 11–83 nm), polydispersity index (range 0.07–0.65); zeta potential (range −3.97 to −19.0) and cloud point (60–85°C) before and after drug loading proves the uniformity and stability of the formulations. SNEDDS formulated with Tween 20 surfactant showed enhanced dissolution with t85% and DE values at 10 min and 78.70, respectively. None of the formulation showed cytotoxicity at the concentration tested. Tween 20 based SNEDDS enhanced permeation of the drug as compared with pure drug across cell lines. It can be concluded that SNEDDS can be formulated by using single non-ionic surfactant system for enhance dissolution and absorption of poorly soluble drug, Atorvastatin calcium.